Gallium nitride vertical power devices on foreign substrates: a review and outlook. (12th June 2018) - Zhang, Yuhao; Dadgar, Armin; Palacios, Tomás
Abstract: Vertical gallium nitride (GaN) power devices have attracted increased attention due to their superior high-voltage and high-current capacity as well as easier thermal management than lateral GaN high electron mobility transistors. Vertical GaN devices are promising candidates for next-generation power electronics in electric vehicles, data centers, smart grids and renewable energy process. The use of low-cost foreign substrates such as silicon (Si) substrates, instead of the expensive free-standing GaN substrates, could greatly trim material cost and enable large-diameter wafer processing while maintaining high device performance. This review illustrates recent progress in material epitaxy, device design, device physics and processing technologies for the development of vertical GaN power devices on low-cost foreign substrates. Although the device technologies are still at the early stage of development, state-of-the-art vertical GaN-on-Si power diodes have already shown superior Baliga's figure of merit than commercial SiC and Si power devices at the voltage classes beyond 600 V. Furthermore, we unveil the design space of vertical GaN power devices on native and different foreign substrates, from the analysis of the impact of dislocation and defects on device performance. We conclude by identifying the application space, current challenges and exciting research opportunities in this very dynamic research field.